Strategies for defending dribbler: Defender and dribbler interaction during a 1-on-1 basketball situation - Fujii, K.; Yamashita, D.; Yoshioka, S.; Kouzaki, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Defenders in 1-on-1 basketball situation anticipate the dribbler`s motion and react to stop the advance. In recent years, researchers have focused on the anticipation in replicated ball game situations by using video clips; however, two problems have been revealed with regard to defending the dribbler: (1) the dribbler`s decision making and (2) the defender`s skilled reaction movement. In the former case, both dribbler and defender should be captured in a real time 1-on-1 situation, instead of on video. In the latter case, split step (Uzu et al., 2009), a preliminary action in which both feet are unweighted, can be one of the skillful reaction movements. The purpose of this study was to reveal how a defender can defend a dribbler in a 1-on-1 basketball situation. Methods: Six basketball players participated in this study as 12 dyads of dribblers and defenders. They played a real-time 1-on-1 game according to the rules of basketball. Three dimensional coordinates of the markers attached on bony landmarks of each player were obtained with a motion capture system. We then calculated for argument as order parameter by using their centre of mass (CoM) medio-lateral displacement, which represents the state of the dyad system, and categorised successful attack trials and effective defence trials. After the categorization, both the dribbler`s and the defender`s peak velocities, time to peak velocities and launch time were obtained by using their CoM medio-lateral velocity and acceleration data. Results & Discussion: The differences in launch time and peak velocity between the dribbler and the defender for the effective defence trials were smaller than that for the successful attack trials. This means that both anticipation and reaction skill are important to effectively defend the dribbler. Additional categorisation of effective defence trials reinforced this idea. After the additional categorising on the basis of the launch time and peak velocity, we found `good anticipation` trials, `split step (good reaction)` trials and `dribbler`s stop` trials. The results suggest that there were three defending strategies and that one strategy would be insufficient, because the defender`s skilled reaction movement and the dribbler`s decision making should be taken into account. In real basketball situations, even if the defender`s anticipation fails, doing a split step may make it possible to defend the dribbler. The dribbler may also stop for many reasons, such as bad ball handling or failure in the dribbler`s decision making.